Implementasi Manajemen Konflik dalam Meningkatkan Produktivitas Madrasah di MTs Al-Washliyah Kota Tebing Tinggi - Amiruddin Siahaan; Neliwati Neliwati; Nadhilah Ajrina (Jurnal Budi Pekerti Agama Islam, 2024)
This research will focus on three main areas: 1) what are the methods of madrasah heads in managing conflict, 2) what is the productivity of madrasahs at MTs al-washliyah, cliff high city, 3) what are the conflict resolution strategies at MTs al-washliyah, cliff high city. This research aims to find out: The first is to find out how school principals manage conflict, the second is to find out how madrasa productivity is at MTs al-Washliyah, Tebing Tinggi City, and the third is to find out what conflict resolution strategies are, This study used qualitative research methods.